An innovative adsorptive chiller prototype based on 3 hybrid coated/granular adsorbers. (1st October 2016) - Sapienza, Alessio; Gullì, Giuseppe; Calabrese, Luigi; Palomba, Valeria; Frazzica, Andrea; Brancato, Vincenza; La Rosa, Davide; Vasta, Salvatore; Freni, Angelo; Bonaccorsi, Lucio; Cacciola, Gaetano
Highlights: We present an innovative adsorption chiller. The machine uses hybrid coated/granular adsorbers. The chiller is based on a new 3 adsorbers layout. The new layout allows a new management strategy with reallocated durations of the isobaric steps. Abstract: In this paper, an innovative adsorptive chiller based on 3 hybrid adsorbers is presented as well as results of the first testing campaign performed under real HVAC operating conditions. The prototype presents two main innovative features aimed to achieve high values of cooling power density: (i) a new architecture, with 3 adsorbers connected to a single evaporator and condenser, that allows to perform an advanced machine's management strategy employing unbalanced durations of the isobaric ads-/desorption steps, (ii) hybrid adsorbers realized embedding microporous Silica Gel loose grains into aluminium finned flat tube heat exchangers previously coated with the Mitsubishi AQSOA FAM Z02 sorbent. Water was selected as refrigerant while up to now the machine operates without any mass/heat recovery. A first testing campaign has been carried out at ITAE labs by a test bench specifically developed for thermally driven chillers. Influence of the cycle time as well as the temperature difference between condenser (TM ) and evaporator (TL ) on the overall performance were highlighted. The experimental measurements showed that the chiller is able to deliver an average cooling power (ACP) ranging between 3.4 and 4.4 kW, a volumetric cooling power (VCP) of 7.25–9.36 kW/m 3, with a COP of 0.3–0.35 at TH = 90 °C, TL ∼ 15–18 °C and TM ∼ 25–28 °C.